A Revolutionary Study Commons and University Library Extension, The Chinese University of Hong Kong. (June 2019) - Fung, S M; Yuen, T
Abstract: The Library Extension completed in 2012 featured a minimalist, sustainable, preservative and conservative design that cleverly integrates a love of nature with respect of history. It echoed with the University's Campus Master Plan and demonstrated how development needs were balanced with preservation concerns. The iconic University Mall and Garden dating back to the 1960s were preserved with an innovative design to provide about 4, 500 m 2 of study area and car parking at basement level. The new extension thus maintained a similar height to the original library building and aligned to the iconic axis along the University Mall. The Mall Garden and Landscape were well preserved with skillful design of skylights under the existing pool. Garden features were surveyed and restored to their original appearances after the basement construction. The campus' much loved house swifts, residing previously on the eaves, were also migrated to the south façade with the introduction of artificial nests. While Green Building design and renewable energy innovations were fully adopted to achieve the highest HKBEAM Platinum standard, the project has provided generous Learning and Research Commons with advanced IT infrastructure which promote causal interactions and knowledge transfer.